2015
DOI: 10.1016/j.meatsci.2015.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Sire breed effect on beef longissimus mineral concentrations and their relationships with carcass and palatability traits

Abstract: The objective of this study was to evaluate sire breed effect on mineral concentration in beef longissimus thoracis (LT) and investigate the correlations between beef mineral concentrations and carcass and palatability traits. Steer progeny (N = 246) from the Germplasm Evaluation project-Cycle VIII were used in this study. In addition to carcass traits, LT was evaluated for mineral concentrations, Warner-Bratzler shear force, and palatability traits. A mixed linear model estimated breed effects on mineral conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…Similar results were obtained in the present study. Duan et al . also reported similar values of Zn (4.1 mg/100 g) in beef, but observed a higher concentration of Fe (3.4 mg/100 g) and lower concentration of Mg (16.4 mg/100 g) than in the present study.…”
Section: Resultssupporting
confidence: 70%
“…Similar results were obtained in the present study. Duan et al . also reported similar values of Zn (4.1 mg/100 g) in beef, but observed a higher concentration of Fe (3.4 mg/100 g) and lower concentration of Mg (16.4 mg/100 g) than in the present study.…”
Section: Resultssupporting
confidence: 70%
“…There was negative relationship with the magnesium and beef flavor but some other minerals have positive relationship with flavor and juiciness. [ 114 , 115 ] …”
Section: Introductionmentioning
confidence: 99%
“…Some reports in muscles from European cattle breeds showed that fat content was negatively correlated with Mg concentration but positively correlated with Fe concentration (Duan et al 2015), and that beef marbling had a negative correlation with Mg concentration, but had positive correlations with Fe and Mn concentrations, and was not related to Na and Cu concentrations (Garmyn et al 2011). Because adipose tissues have extremely less mineral content than does lean beef, it is likely that lower mineral concentrations generally reflect higher fat contents in muscles.…”
Section: The Relationships Of Mineral Concentrations With Physicochemmentioning
confidence: 99%
“…; Duan et al . ). Because subcutaneous and intramuscular adipose tissues have extremely less mineral content than does lean beef (Ministry of Education, Culture, Sports, Science and Technology ), it is natural to consider that mineral concentrations decrease with increasing amounts of fat in muscles.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation